UNESCO-Weltkulturerbe und der Gedanke der Nachhaltigkeit - Seng, Eva- Maria (UNESCO heute. ZS der Deutschen UNESCO-Kommission)

Stadterweiterungen, Kirchenneubau und Pfarrgründungen im 19. Jahrhundert - Seng, Eva- Maria (Die Pfarre in der Stadt. Siedlungskern – Bürgerkirche – Urbanes Zentrum (Reihe: Städteforschung, Veröffentlichungen des Instituts für vergleichende Städtegeschichte in Münster Bd. 82))

The car sharing problem - Briest, Patrick; Raupach, Christoph (Proceedings of the 23rd ACM symposium on Parallelism in algorithms and architectures - SPAA '11)

Verfahren zur redundanten Datenplatzierung in skalierbaren Speichersystemen - Effert, Sascha

Stabilized Mixed Triangular and Tetrahedral Finite Elements with Volume and Area Bubble Functions - Caylak, Ismail

Towards Duality of Multicommodity Multiroute Cuts and Flows: Multilevel Ball-Growing - Kolman, Petr; Scheideler, Christian (28th International Symposium on Theoretical Aspects of Computer Science, STACS 2011, March 10-12, 2011, Dortmund, Germany)

Von Taschentüchern und anderen Dingen, oder: Die “akute Einsamkeit des Menschen”. Herta Müller und der Widerspruch - Eke, Norbert Otto (literatur für leser)

Spiegel/Bilder – Werner Fritschs Anatomie von Terror und Krieg - Eke, Norbert Otto (Terror und Form (Limbus. Australisches Jahrbuch für germanistische Literatur- und Kulturwissenschaft. Band 4))

“Gelber Mais, keine Zeit”. Herta Müllers Nach-Schrift Atemschaukel. Roman - Eke, Norbert Otto (GegenwartsLiteratur. Ein germanistisches Jahrbuch/A German Studies Yearbook 10/2011)

Wahre, unzeitige und falsche Aufklärung. Fortschreibungen einer ‘alten’ Debatte im Kontext der Französischen Revolution - Eke, Norbert Otto (“Das Leben in der Poesie”. Festschrift für Magdolna Orosz zum 60. Geburtstag)

Dem “Haufen genügt die Täuschung”. Georg Forster und das Theater - Eke, Norbert Otto (Georg-Forster-Studien)
Angaben zur Herausgeberschaft: Hg. im Auftrag der Georg-Forster-Gesellschaft von Stefan Greif und Michael Ewert Angabe zum Ort: Kassel

“Blühe, deutsches Vaterland”. Hoffmann von Fallerslebens ‘volkstümliche’ Hymne und die ‘deutsche’ Hymnenpraxis - Eke, Norbert Otto (Der Deutschunterricht 63, H. 3: Literatur und Musik)

Welt-Kunst-Beobachtung. Rainald Goetz und das Theater - Eke, Norbert Otto (Text + Kritik, H. 190)

Approximation Techniques for Utilitarian Mechanism Design - Briest, Patrick; Krysta, Piotr; Vöcking, Berthold (SIAM Journal on Computing)
This paper deals with the design of efficiently computable incentive-compatible mechanisms for combinatorial optimization problems with single-minded agents each possibly having multiple private parameters. We focus on approximation algorithms for NP-hard mechanism design problems. These algorithms need to satisfy certain monotonicity properties to ensure truthfulness. Since most of the known approximation techniques do not fulfill these properties, we study alternative techniques. Our first contribution is a quite general method to transform a pseudopolynomial algorithm into a monotone fully polynomial time approximation scheme (FPTAS). This can be applied to various problems like, e.g., knapsack, constrained shortest path, or job scheduling with deadlines. For example, the monotone FPTAS for the knapsack problem gives a very efficient, truthful mechanism for single-minded multiunit auctions. The best previous result for such auctions was a 2-appro-xi-ma-tion. In addition, we present a monotone PTAS for the generalized assignment problem with any constant number of private parameters per agent. The most efficient way to solve packing integer programs (PIPs) is linear programming–based randomized rounding, which also is in general not monotone. We show that primal-dual greedy algorithms achieve almost the same approximation ratios for PIPs as randomized rounding. The advantage is that these algorithms are inherently monotone. This way, we can significantly improve the approximation ratios of truthful mechanisms for various fundamental mechanism design problems like single-minded combinatorial auctions (CAs), unsplittable flow routing, and multicast routing. Our primal-dual approximation algorithms can also be used for the winner determination in CAs with general bidders specifying their bids through an oracle.

Buying Cheap Is Expensive: Approximability of Combinatorial Pricing Problems - Briest, Patrick; Krysta, Piotr (SIAM Journal on Computing)
We investigate nonparametric multiproduct pricing problems, in which we want to find revenue maximizing prices for products $\mathcal{P}$ based on a set of customer samples $\mathcal{C}$. We mostly focus on the unit-demand case, in which products constitute strict substitutes and each customer aims to purchase a single product. In this setting a customer sample consists of a number of nonzero values for different products and possibly an additional product ranking. Once prices are fixed, each customer chooses to buy one of the products she can afford based on some predefined selection rule. We distinguish between the min-buying, max-buying, and rank-buying models. Some of our results also extend to single-minded pricing, in which case products are strict complements and every customer seeks to buy a single set of products, which she purchases if the sum of prices is below her valuation for that set. For the min-buying model we show that the revenue maximization problem is not approximable within factor $\mathcal{O}(\log^{ε}|\mathcal{C}|)$ for some constant $ε>0$, unless $NP\subseteqDTIME(n^{\mathcal{O}(\log\log n)})$, thereby almost closing the gap between the known algorithmic results and previous lower bounds. We also prove inapproximability within $\mathcal{O}(\ell^{ε})$, $\ell$ being an upper bound on the number of nonzero values per customer, and $\mathcal{O}(|\mathcal{P}|^{ε})$ under slightly stronger assumptions and provide matching upper bounds. Surprisingly, these hardness results hold even if a price ladder constraint, i.e., a predefined order on the prices of all products, is given. Without the price ladder constraint we obtain similar hardness results for the special case of uniform valuations, i.e., the case that every customer has identical values for all the products she is interested in, assuming specific hardness of the balanced bipartite independent set problem in constant degree graphs or hardness of refuting random 3CNF formulas. Introducing a slightly more general problem definition in which customers are given as an explicit probability distribution, we obtain inapproximability within $\mathcal{O}(|\mathcal{P}|^{ε})$ assuming $NP\nsubseteq\bigcap_{δ>0}BPTIME(2^{\mathcal{O}(n^{δ})})$. These results apply to single-minded pricing as well. For the max-buying model a polynomial-time approximation scheme exists if a price ladder is given. We give a matching lower bound by proving strong NP-hardness. Assuming limited product supply, we analyze a generic local search algorithm and prove that it is 2-approximate. Finally, we discuss implications for the rank-buying model.

Dissociation in changes in EMG activation during maximal isometric and submaximal low force dynamic contractions after exercise-induced muscle damage. - Plattner, K; Baumeister, Jochen; Lamberts, RP; Lambert, MI (J Electromyogr Kinesiol)

From lab to field conditions: A pilot study on EEG methodology in applied sports sciences - Reinecke, K; Cordes, M; Lerch, C; Schubert, M; Koutsandreou, F; Weiss, M; Baumeister, Jochen (Appl Psychophysiol Biofeedback)

Effectiveness of injury prevention programs in female youth soccer: a systematic review - Lerch, C; Cordes, M; Baumeister, Jochen

Dissociation in changes in EMG Activation during maximal isometric and submaximal low force dynamic contractions after exercise induced muscle damage - Plattner, T; Baumeister, Jochen; Lamberts, RP; Lambert, MI (Abstract Book - 16th Annual Congress of the European College of Sports Science)

Brain activity during motor control is not influenced after exhaustive strength training - Reinecke, K; Schubert, M; Schade, J; Weiß, M; Baumeister, Jochen (Fatigue: An Interdisciplinary approach)